Elevated TyG Index Predicts Progression of Coronary Artery Calcification - Park, Kahui; Ahn, Chul Woo; Lee, Sang Bae; Kang, Shinae; Nam, Ji Sun; Lee, Byoung Kwon; Kim, Jung Hye; Park, Jong Suk (Diabetes care, 2019)
To investigate the triglyceride-glucose (TyG) index association with coronary artery calcification (CAC) progression in adult Koreans. Various cardiovascular risk factors and anthropometric profiles were assessed in 1,175 subjects who previously had a CAC evaluation at least twice by multidetector computed tomography in a health care center. The TyG index was determined using ln(fasting triglycerides [mg/dL] × fasting glucose [mg/dL]/2). The CAC progression was defined as either incident CAC in a CAC-free population at baseline or an increase of ≥2.5 units between the square roots of the baseline and follow-up coronary artery calcium scores (CACSs) of subjects with detectable CAC at baseline. CAC progression was seen in 312 subjects (27%) during 4.2 years follow-up. On the basis of the TyG index, subjects were stratified into three groups. Follow-up CACS and incidence of CAC progression were markedly elevated with rising TyG index tertile. Logistic regression analysis adjusted for various risk factors revealed an odds ratio for CAC progression of 1.82 (95% CI 1.20-2.77; ≤ 0.01) when the highest and lowest TyG index tertiles were compared. The TyG index is an independent predictor of CAC progression.